Transcriptomic profiling revealed important roles of amino acid metabolism in fruiting body formation at different ripening times in Hypsizygus marmoreus - Xiang, Quanju; Arshad, Muhammad; Li, Yakun; Zhang, Huijuan; Gu, Yunfu; Yu, Xiumei; Zhao, Ke; Ma, Menggen; Zhang, Lingzi; He, Maolan; Chen, Qiang (Frontiers in Microbiology, 2023)
Hypsizygus marmoreus is an industrial mushroom that is widely cultivated in East Asia. Its long postripening stage before fruiting severely limits its industrialized production. In this study, five different mycelial ripening times (30, 50, 70, 90, and 100 d) were chosen and primordia (30P, 50P, 70P, 90P and 110P) were collected for comparative transcriptomic analyses. The corresponding substrates (30F, 50F, 70F, 90F, and 110F) were used for nutrient content and enzyme activity determination. In pairwise comparisons between 110P and other primordia, a total of 1,194, 977, 773 and 697 differentially expressed genes (DEGs) were identified in 30P-110P, 50P-110P, 70P-110P, and 90P-110P, respectively. Gene Ontology (GO) and Kyoto Encyclopedia of Genes Genomes (KEGG) functional enrichment analyses revealed that the DEGs were mainly associated with amino acid metabolism, and lipid and carbohydrate metabolism pathways. Tyrosine, tryptophan, phenylalanine and histidine metabolism were enriched in all groups. Among the main carbon nutrients, the contents of cellulose and hemicellulose were high, and the lignin content decreased with the extension of the ripening time. Laccase had the highest activity, and acid protease activity decreased with the extension of the ripening time. These results will provide a basis for the optimization of its cultivation.